Mordida aberta pelo uso prolongado da chupeta: educar para prevenir - Cremonesi, Luciana Lindolpho (2015)
The anterior open bite (MMA) is a complex anomaly that is difficult to treat. It is characterized by a lack of vertical contact between the teeth of the upper and lower arches, being the opening of different sizes. This condition can be regarded as a deviation in the vertical relationship of the upper and lower maxillary arches. Patients with MAA may also have poor lip contact, mouth breathing, atypical phonation, maxillary arch constriction, inflamed gums, large lower face, open mandibular branch, inclined mandibular plane, long clinical crowns, thin and elongated symphysis, increased occlusal plan, small mandibular body, mandibular retraction, and tendency to be Class II malocclusion. The etiology is multifactorial and is almost always associated with orofacial myofunctional disharmony, either by genetic factors or the long-acting non-nutritive deleterious oral habits (pacifier sucking and finger sucking). Objectives: evaluate the level of information of first-time moms and pregnant women who already have children about oral habits; propose the makingof an educational booklet about the complications caused by non-nutritive oral habits in children to be available to users of the public health service of the city of Bauru (state of Sao Paulo). Tools and Methodology: a questionnaire was administered to first-time moms and pregnant women who already have children, cared by Bauru’s public health system, with questions related to breastfeeding practices in relation to non-nutritive oral habits. Results: presented by absolute and relative frequencies (%) in tables and application of statistical test Chi-square for association between the two groups of pregnant women. Conclusions: Most of the respondents are unaware of the diseases, caused by oral habits of non-nutritive sucking; conducting educational work for mothers and future mothers about the importance of breastfeeding and the time required for it; there is a need to propose the making of an educational booklet to provide parents and caregivers a clarification about deleterious oral habits and the resulting malocclusion type MAA.